A production and operations management study on the inventory management of Cello's Donuts amd Dips - Cabreros, Celeste Joy (College of Engineering, 2005)
The present food industry is currently faced with the challenge of producing frivolous, less nourishing food products to chase customer wants. With this challenge, the emergence of food industries that capitalize and specialize in this aspect are starting to flood the market. These new industries, however, though offering good service in the food market with their noble products, are not yet stable in terms of demand. Operations Management is then needed to put everything into balance. Cello's Dips and Doughnuts is just one of the many companies that recently established its business in the food market. With the problem of tracking its inventory and managing it properly, this study specifically aims to evaluate the existing company process, recommend more appropriate techniques specifically on the company's inventory system and provide an easy way of conducting forecasts and tracking inventory levels. The group initially developed a forecasting technique with the use of trends to suit the company's inventory scenario of having a fixed reorder quantity for a varying demand. From the ABC Approach, it was found out that milk, eggs and butter are the raw materials contributing to 82.73% of the company's daily cost for raw materials. This means that these three raw materials should be properly tracked and controlled. Thee raw materials should be ordered with amounts equal to the economic order quantity, Q, at a time when the reorder point, R, is reached. The following values are the Q and R levels for the three raw materials: 27 and 18 liters of milk, 10 and 6 trays for eggs, and 32 and 15 bars for butter. This means that when the current inventory level reaches R, the company should call its supplier to order Q and require them to deliver the placed orders not later that the specified lead time of each raw material. Simulating the computed Q and R using Excel, it was shown that costs of having the three important raw materials in the production of doughnuts were improved. Costs of the actual and proposed inventory cost, in peso values, are as follows: 2263.48 to 1160.30 for milk, 967.25 to 897.35 for eggs and 1014.24 to 909.23 for butter. Having these values at hand, the group suggests that implementation of the proposed inventory management. However, intensive tracking is needed in order to address demand changes. To provide ease in forecasting and tracking of the inventory levels, the group created automated software that computes for the values of the succeeding forecasts, Q and R given the past sales data and the changing costs of holding and procurement of goods.